Implications of the diagnostic criteria of idiopathic pulmonary fibrosis in clinical practice: Analysis from the Australian Idiopathic Pulmonary Fibrosis Registry. Issue 4 (17th October 2018) - Jo, Helen E.; Glaspole, Ian; Goh, Nicole; Hopkins, Peter M.A.; Moodley, Yuben; Reynolds, Paul N.; Chapman, Sally; Walters, Eugene Haydn; Zappala, Christopher; Allan, Heather; Macansh, Sacha; Grainge, Christopher; et al.
ABSTRACT: Background and objective: Current guidelines for the diagnosis of idiopathic pulmonary fibrosis (IPF) provide specific criteria for diagnosis in the setting of multidisciplinary discussion (MDD). We evaluate the utility and reproducibility of these diagnostic guidelines, using clinical data from the Australian IPF Registry. Methods: All patients enrolled in the registry undergo a diagnostic review whereby international IPF guidelines are applied via a registry MDD. We investigated the clinical applicability of these guidelines with regard to: (i) adherence to guidelines, (ii) Natural history of IPF diagnostic categories and (iii) Concordance for diagnostic features. Results: A total of 417 participants (69% male, 70.6 ± 8.0 years) with a clinical diagnosis of IPF underwent MDD. The 23% of participants who did not meet IPF diagnostic criteria displayed identical disease behaviour to those with confirmed IPF. Honeycombing on radiology was associated with a worse prognosis and this translated into poorer prognosis in the 'definite' IPF group. While there was moderate agreement for IPF diagnostic categories, agreement for specific radiological features, other than honeycombing, was poor. Conclusion: In clinical practice, physicians do not always follow IPF diagnostic guidelines. We demonstrate a cohort of IPF patients who do not meet IPF diagnostic guideline criteria, based largely on their radiology and lack of lung biopsy, but who have outcomes identical to those with IPF. Abstract : In clinical practice, physicians may assign a diagnosis of idiopathic pulmonary fibrosis (IPF) in patients who are sufficiently similar in their presentation to IPF but who do not strictly fulfil IPF diagnostic criteria. Our study shows that these patients demonstrate identical disease progression and survival to those who fulfil diagnostic criteria. See related Editorial